A general numerical approximation of the stress characteristic field at a singular point - Nor Alisa, Mohd Damanhuri; Nor Syafikah, Ayob (Universiti Malaysia Pahang, 2018)
A general numerical approximation for the construction of the stress characteristic field in the deformation of ideal granular material at a singular point is considered. The self weight of the granular material is neglected and the stresses are assumed to obey the Coulomb yield criterion. A numerical approximation using finite difference method is used to solve a boundary value problem that leads to the construction of a complete stress characteristic field. The method is presented in this paper and tests, within the MATLAB program at each stage of the construction.